Moretiana Adversa y próspera fortuna de Agustín Moreto - Lobato, Maria Luisa; Martínez Berbel, Juan Antonio (Iberoamericana Vervuert, 2008)
This work presents a new vision of his dramaturgy inserted in the theatrical company of the seventeenth century.